'The Ghost in the Machine': Thomas Koschat and the volkstümlich in Mahler's Fifth Symphony. Issue 3 (2nd July 2018) - Barham, Jeremy
Abstract : This article offers a solution to a long-standing mystery surrounding the identity of a melody by Carinthian folkloric composer Thomas Koschat used by Mahler in his Fifth Symphony. It first places such musical reference in the broader scholarly context of Mahler and the volkstümlich . Evidence surrounding the chronology and sketches of the symphony as well as Mahler's intersection with Koschat and the latter's reception is assessed. Musical materials are analysed in order to identify the source of borrowing in Koschat's Liederspiel Am Wörther See (1880), and to understand the key structural and expressive roles it plays in Mahler's work. The article concludes by reflecting on the possible socio-cultural meaning and significance of this case of Mahlerian allusive practice.